2019
DOI: 10.1177/2325967119853218
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Proximal Hamstring Tendon Repair: A Systematic Review

Abstract: Background: Previous studies have evaluated functional outcomes and return-to-sport rates after proximal hamstring tendon (HT) repair. Purpose: To systematically review the literature in an effort to evaluate return-to-sport rates after proximal HT repair. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was performed by searching PubMed, the Cochrane Library, and Embase to identify studies that evaluated postoperative lower extremity function and return-to-sport rates in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Belk et al. [ 36 ] concluded in a systematic review that patients with partial and complete hamstring tears can be expected to return to sports at a similar rate after operative repair (partial 96.8% and complete 93.0%, p =.18), which was similar finding with the systematic review authored by Coughlin et al. [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Belk et al. [ 36 ] concluded in a systematic review that patients with partial and complete hamstring tears can be expected to return to sports at a similar rate after operative repair (partial 96.8% and complete 93.0%, p =.18), which was similar finding with the systematic review authored by Coughlin et al. [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
“…Belk et al. [ 36 ] found that the early repair group had the quickest time to return to sports and the highest rate of return to sports, but statistical significance was not reached in neither of these outcomes. Coughlin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Belk et al 19 and Coughlin et al 3 performed systematic reviews to look specifically at return to sport after surgical treatment of proximal hamstring tears. 3 19 Both studies had similar conclusions suggesting a high rate of sport participation.…”
Section: Resultsmentioning
confidence: 99%
“…Their main outcome was a return to sport, which was achieved in the majority of patients treated surgically. 3 Belk (2019) 19 included 16 studies and had similar conclusions with a return to sport in greater than 90% of the patients having a hamstring repair.…”
Section: Current Evidencementioning
confidence: 94%
See 1 more Smart Citation